2021
DOI: 10.1002/biot.202000657
|View full text |Cite
|
Sign up to set email alerts
|

Advances in production and structural derivatization of the promising molecule ursolic acid

Abstract: Ursolic acid (UA) is a ursane‐type pentacyclic triterpenoid compound, naturally produced in plants via specialized metabolism and exhibits vast range of remarkable physiological activities and pharmacological manifestations. Owing to significant safety and efficacy in different medical conditions, UA may serve as a backbone to produce its derivatives with novel therapeutic functions. This review aims to provide ideas for exploring more diverse structures to improve UA pharmacological activity and increasing it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 114 publications
0
4
0
Order By: Relevance
“…The switch of traditional chemical manufacturing towards green biological manufacturing supersedes the existing “high energy consumption, high emissions” model and dependence on fossil resources (Clark et al, 2012) for the synthesis of valuable compounds. For example, enzyme catalysis and construction of microbial cell factories to biosynthesize Glycyrrhetinic acid (Ahmad et al, 2020; Xu et al, 2021), Diosgenin (Abbas et al, 2021), Ursolic acid and its derivatives (Liu et al, 2021). In addition, employing renewable biomaterials with low CO 2 emission to replace fossil fuel resources has become the global attention to develop green, renewable, safe, and controllable biological manufacturing as a primary goal of human society.…”
Section: Introductionmentioning
confidence: 99%
“…The switch of traditional chemical manufacturing towards green biological manufacturing supersedes the existing “high energy consumption, high emissions” model and dependence on fossil resources (Clark et al, 2012) for the synthesis of valuable compounds. For example, enzyme catalysis and construction of microbial cell factories to biosynthesize Glycyrrhetinic acid (Ahmad et al, 2020; Xu et al, 2021), Diosgenin (Abbas et al, 2021), Ursolic acid and its derivatives (Liu et al, 2021). In addition, employing renewable biomaterials with low CO 2 emission to replace fossil fuel resources has become the global attention to develop green, renewable, safe, and controllable biological manufacturing as a primary goal of human society.…”
Section: Introductionmentioning
confidence: 99%
“…Ursolic acid is widely used as an anti-inflammatory drug, and many biological experiments have demonstrated that ursolic acid can play an anti-inflammatory role in a variety of diseases, including both oncological and non-oncological diseases [36,37]. Clinical trials are now being carried out to verify its efficacy and safety [38].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it should be noted that antimicrobial surface agents can inhibit biofilm formation for example via quorum sensing [77] or cyclic di-GMP (c-di-GMP) signaling interference, of which the latter is an intracellular signaling molecule of bacteria [78]. Quorum sensing (QS) is an intra-and intercellular mechanism, which facilitates the communication between cells and the interaction between the environment and cells [79].…”
Section: Antimicrobial Stainless Steel Surfacesmentioning
confidence: 99%